The Impact of the 2023 Cashless Policy on Live Music Performance in Nigeria: A Study of Selected Popular Musicians and Audience - Akande, Sunday Olufemi (NIU Journal of Humanities, 2024)
A live music performance is an event where musicians perform in front of an audience, playing instruments or singing live. The cashless policy in Nigeria is a policy established by the Central Bank of Nigeria (CBN) to curb excesses in the handling of cash in the Nigerian federation. The policy was enforced not to eliminate the use of cash, but to reduce the volume of cash in circulation. This study reflects on the problems and prospects associated with the live music performances during the 2023 cashless policy in Nigeria. The study employed both primary and secondary data. The primary includes journal, books, internet and magazine. It also relied on interview and participant observation method. Findings revealed that the cashless policy was very hard-hitting especially for musicians whose brands are based on the money they are being sprayed at events. For them, it has been bad business since people have been unable to spray them at events during the cashless policy. It conclusion, the exchange for money between a live music performer and an audience through cash is a changing landscape that is left presently, only with the option of appreciating a musician through bank online transactions but calls for emerging a fascinating digital method of appreciation Keywords: Cashless Policy, Live Music, Musicians, Performance.